Comparison of the Conception Of Property Rights in Terms of Islamic Civil and Civil Law - Aip Piansah (Yayasan Mentari Madani, 2023)
Property rights are one part of human rights that have been regulated in the laws and regulations in Indonesia. Ownership can be owned by anyone who is entitled and valid according to written regulations. The focus of this discussion is to look for similarities and differences in the rules of the concept of property rights in terms of civil law (BW) and Islamic civil law (fiqh)). Property rights are regulated in the Third Chapter of Articles 570 – 624 of the Civil Code. Article 570 of the Civil Code explains that